2018
DOI: 10.3390/agriculture8040056
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Agronomic Practice on the Control of Wheat Leaf Diseases

Abstract: Soil tillage and crop rotation are considered important tools in wheat leaf disease control; however, the results of investigations are inconsistent. The aim of the present study was to determine the effect of the soil tillage system and cropping sequence on the development of winter wheat leaf diseases in 2012-2017. The disease development was assessed in a two-factor experiment: (a) soil tillage system; and (b) crop rotation. Foliar fungicides were used uniformly in all variants. The results showed that tan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 16 publications
3
31
0
5
Order By: Relevance
“…Most studied cultural methods are crop rotation and tillage; however, the results are contradictory. They show that crop rotation and an efficient residue management are effective tools for reducing tan spot in winter wheat (Cotuna et al, 2015); however, in a study conducted in Latvia, the previous crop did not significantly affect the level of Septoria leaf blotch (Bankina et al, 2018). In a repeated wheat sowing, tan spot infection started earlier (Bankina et al, 2018) (Bankina et al, 2018).…”
Section: The Impact Of Cultural Methods On Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studied cultural methods are crop rotation and tillage; however, the results are contradictory. They show that crop rotation and an efficient residue management are effective tools for reducing tan spot in winter wheat (Cotuna et al, 2015); however, in a study conducted in Latvia, the previous crop did not significantly affect the level of Septoria leaf blotch (Bankina et al, 2018). In a repeated wheat sowing, tan spot infection started earlier (Bankina et al, 2018) (Bankina et al, 2018).…”
Section: The Impact Of Cultural Methods On Diseasesmentioning
confidence: 99%
“…The level of Septoria leaf blotch was significantly lower and exceeded the severity of tan spot only in 2015. Powdery mildew was observed every year; however, the disease severity never reached 2% during the evaluation (Bankina et al, 2018).…”
Section: Winter Wheat Leaf Diseasesmentioning
confidence: 98%
See 2 more Smart Citations
“…It is reported that one of the main reasons why farmers do not want to grow pulses is unstable and more variable yield in comparison to non-legume crops in Europe (Cernay et al, 2015). Traditional soil tillage helps to limit harmful organisms like wheat leaf diseases (Bankina et al, 2018) and weeds (Ausmane, Melngalvis, & Ruža, 2017), but is more time and energy consuming if compared to minimum soil tillage treatments (Strašil, Vach, & Smutný, 2015). In different studies, contradictory results are reported on advantages of soil tillage method (traditional or reduced) to ensure a higher yield and/or quality of wheat (e.g.…”
Section: Introductionmentioning
confidence: 99%